The Legal Effects of Ratification of Preventive Composition of Bankruptcy - امين, خالص نافع; نعمة, جواد كاظم (Journal of Legal Sciences, 2019)
The preventive composition of bankruptcy does not become binding on its parties despite the consent of the debtor and majority of creditors shall only ratify by the court, once the ratification becomes effective and produces its effects, the trader debtor must commit to the terms of the conciliation agreed upon by the conciliation society, a natural person or company, the validity of conciliation prevents the debtor from requesting another composition and also prevents those who commits with the debtor to fulfil the benefit of the conditions of the composition.However, the partners in the company who are responsible for all of their money for its debts are subject to the effects of a protective settlement and will benefit from the conditions of the composition, for the debtor and those who are bond by the debtor to fulfil.